Nonaddictive habit formation and the equity premium puzzle - Milind M. Shrikhande (Federal Reserve Bank of Atlanta, 1996)
I analyze a model in a simple representative-agent economy with one risky and one riskless asset, populated by habit-forming consumer-investors. These consumer-investors exhibit nonaddictive habit formation in the sense that the current consumption rate of the consumer-investors can fall below the habit-forming past consumption rate. I endogenize the real riskless rate of return in this representative-agent economy and find that the equity premium puzzle is resolved for values of the coefficient of relative risk aversion, the discount rate, and the intensity of nonaddictive habit formation, which are validated by previous empirical or survey-based studies. Nonaddictive habit formation studied here complements and extends current research on habit-forming preferences. Given a constant investment opportunity set, I find that the real riskless rate in the economy increases with relative risk aversion of the consumer and decreases as the habit formation intensity increases. The historically observed volatility of the real riskless rate is matched for one set of parameter values. Extensions with time-varying investment opportunity sets could explain the low risk-free rate and the relatively large variability of the market return over the variability of the risk-free rate through time.
Keywords: 330; Stock - Prices